2023
DOI: 10.1001/jamanetworkopen.2023.9747
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence–Enabled Analysis of Statin-Related Topics and Sentiments on Social Media

Abstract: ImportanceDespite compelling evidence that statins are safe, are generally well tolerated, and reduce cardiovascular events, statins are underused even in patients with the highest risk. Social media may provide contemporary insights into public perceptions about statins.ObjectiveTo characterize and classify public perceptions about statins that were gleaned from more than a decade of statin-related discussions on Reddit, a widely used social media platform.Design, Setting, and ParticipantsThis qualitative stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Our AI-enabled analysis of public perceptions of CAC testing demonstrates how well our previously described algorithm for topic modeling generalizes to another clinical domain 8 . A powerful aspect of our pipeline is leveraging techniques in unsupervised machine learning that obviate the need for topic prespecification, which allows discovery of previously unexpected ideas (e.g., non-evidence-based use of CAC).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Our AI-enabled analysis of public perceptions of CAC testing demonstrates how well our previously described algorithm for topic modeling generalizes to another clinical domain 8 . A powerful aspect of our pipeline is leveraging techniques in unsupervised machine learning that obviate the need for topic prespecification, which allows discovery of previously unexpected ideas (e.g., non-evidence-based use of CAC).…”
mentioning
confidence: 83%
“…Details around topic modeling and sentiment analysis in this paper are described elsewhere 8 . Briefly, after preprocessing, discussions are embedded into a numerical representation using a pretrained, sentence-level Bidirectional Encoder Representations from Transformers (BERT) model called all-MiniLM-L6-v2 19 , which has been trained on over 600 million Reddit posts and a dataset containing over 12 million papers from medical journals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Misinformation is an important driver of nonuse and is prevalent in online forums, affecting patients and clinicians alike. 8 , 9 , 10 …”
mentioning
confidence: 99%
“… 11 A recent analysis of Reddit data found that the average sentiment of statin‐related content was neutral to negative and that the most common themes were alternative lipid‐lowering methods, adverse effects, and statin hesitancy. 10 Compared with Reddit, Twitter is even more widely used. 12 Twitter is among the most influential social media platforms, with ≈145 million daily users and 330 million monthly users.…”
mentioning
confidence: 99%